Sex-specific determinants of serum 25-hydroxyvitamin D3 concentrations in an elderly German cohort : a cross-sectional study - Jungert, Alexandra; Neuhäuser-Berthold, Monika; Justus Liebig University Giessen (My University, 2015)
BACKGROUND: Considering the suggested link between vitamin D insufficiency and several chronic diseases, attention should be given to approaches for improving vitamin D status. Elderly subjects are regarded as a high-risk group for developing an insufficient vitamin D status. Socioeconomic, dietary, lifestyle and environmental factors are considered as influencing factors, whereupon sex differences in predictors of vitamin D status are rarely investigated. The purpose of this study is to identify the main predictors of serum 25-hydroxyvitamin D3 [25(OH)D3] concentrations in elderly subjects by taking into account potential sex differences. METHODS: This is a cross-sectional study in 162 independently living German elderly aged 66 to 96years. Serum 25(OH)D3 concentrations were assessed by an electrochemiluminescence immunoassay. Multiple regression analyses were performed to identify predictors of 25(OH)D3 concentrations stratified by sex.RESULTS:Median 25(OH)D3 concentration was 64nmol/L and none of the subjects had 25(OH)D3 concentrations<25nmol/L. In women, intact parathyroid hormone (iPTH) (beta=-0.323), % total body fat (beta=-0.208), time spent outdoors (beta=0.328), month of blood sampling (beta=0.229) and intake of vitamin D supplements (beta=0.172) were the predominant predictors of 25(OH)D3, whereas in men, iPTH (beta=-0.254), smoking (beta=-0.282), physical activity (beta=0.336) and monthly household net income (beta=0.302) predicted 25(OH)D3 concentrations. The final regression models accounted for 30% and 32% of the variance in 25(OH)D3 concentrations in women and men, respectively. CONCLUSION: The findings indicate that 25(OH)D3 concentrations are influenced by body composition, month of blood sampling, economic factors, lifestyle, supplement intake and iPTH, but may not be associated with age, sex, dietary factors, kidney function and presence of selected chronic diseases in community-dwelling elderly. Furthermore, our results provide evidence for sex-specific determinants of the vitamin D status, which ought to be considered for preventive strategies.
Keywords: 25-hydroxyvitamin D; determinants; lifestyle; body composition; diet; ddc:610